PECULIARITIES OF ORGANIZATION OF WORK RELATED TO EDUCATION IN MEDICAL TECHNICAL SCHOOL STUDENTS - Xaitbayeva , Nodira Abduvaxidovna (Educational Research in Universal Sciences, 2024)
This article talks about the theoretical explanation of the organization of educational work in medical technical schools to acquire the theoretical knowledge and practical technical skills necessary for various healthcare roles, and describes the educational system of educational institutions.